Conceptual understanding of myths and legends in Malay history - Hussain Othman, (Universiti Kebangsaan Malaysia, 2008)
Malay historical texts are also rich in the mythical and legendary stories. Unfortunately, many scholars who study the content of the texts have always misunderstood them. In their study, they specify on the superficial aspects, instead of functional and historical aspects of the mythical and legendary stories. It is the purpose of this paper to explore my conceptual understanding of mythological and legendary stories in the Malay classical historical texts to prove that there are indeed historical truth embedded within these stories. To do that, Sejarah Melayu, Hikayat Raja-raja Pasai and Hikayat Merong Mahawangsa are selected